PENGARUH KERJA SAMA TIM TERHADAP KEBERHASILAN PENYELESAIAN TUGAS KELOMPOK MAHASISWA - Aprodegreselia Tarigan; Darwis Robinson Manalu (STKIP Subang, 2026)
Teamwork is a crucial skill that helps students complete group projects. However, differences in participation levels, communication, responsibility, and task allocation often hinder collaborative learning. This study aims to analyze the impact of team collaboration on the success of students' group assignment completion. This study employed a quantitative approach using a survey method, distributing questionnaires to 105 active students with experience completing group projects. Data analysis was performed using IBM SPSS through validity, reliability, normality, simple linear regression analysis, partial t-tests, and the coefficient of determination (R²). The research findings indicate that team collaboration has a positive and significant effect on the success of group assignment completion. The regression equation obtained is Y = 6.285 + 0.763X, indicating that each increase in team collaboration is accompanied by an increase in the success of group assignment completion. The t-test results showed a significance value of 0.000 (<0.05), thus supporting the research hypothesis. The coefficient of determination (R²) of 0.525 indicates that team collaboration can explain 52.5% of the variation in the success of group assignment completion, while the remaining 47.5% is influenced by other factors not included in the study. This study indicates that communication, coordination, active participation, responsibility, and efficient task distribution are crucial elements in increasing the success of student group assignment completion.